Pseudodarwinizm selekcjonistycznych modeli rozwoju nauki - Wagner, Michał (Filozofia Nauki, 2022)
The paper analyzes the incompatibility of Evolutionary Epistemology of Theories (EET) with Charles Darwin’s theory of evolution. The argument consists of four parts, each addressing a specific problem with EET and offering examples. Firstly, advocates of EET frequently misapply Darwin’s theory by asserting that evolution is teleological, which is at odds with Darwinism. Secondly, the “universal Darwinism” underlying EET is inconsistent with the relativism present in Darwin’s theory. Thirdly, because of the relativistic character of Darwin’s theory, philosophies that appeal to it need to provide additional justification for using Darwin’s ideas outside of biology, which EET fails to do. Finally, the paper demonstrates that the Darwinocentric historiography proposed by EET underappreciates neo-Lamarckism, whose model of evolution is closer to that used in EET.